Construção e validação de instrumento para avaliação da qualidade das farmácias comunitárias e dos serviços ofertados - Laurentino, Elias Matias (2024)
In Brazil, the lack of standardized instruments to assess the quality of community pharmacies (CP) represents an important gap in identifying opportunities for improvements that promote the provision of quality services and provide safety to customers. Thus, the objective was to construct and validate the content of an instrument to assess the quality of CP and the services offered. A scoping review, an integrative review, and a documentary survey were conducted to identify the quality criteria assessed globally in CP, the instruments and questions used; the barriers to the provision of quality services in Brazilian CP; and the main regulations related to the structure, operation, and quality assessment of CP in Brazil. A prototype of the instrument was developed, evaluated, and adjusted, and submitted to content validation by experts using the Delphi technique (2 rounds). The experts assessed the questions regarding their relevance for quality assessment, pertinence within each category/subcategory, clarity, and feasibility. Content validity was calculated using the content validity index (CVI), and inter-rater agreement was calculated using Gwet's first-order concordance coefficient (CA1). The scoping review analyzed 64 studies, identifying 7 categories and 36 subcategories, with emphasis on “pharmaceutical services”, “dispensing processes” and “infrastructure”. The integrative review examined 32 studies, identifying barriers such as over-the-counter medication delivery by untrained professionals and inadequate infrastructure. The documentary research analyzed 58 regulatory acts, highlighting the importance of drug safety and regulation, compliance with documentation and infrastructure. The prototype, with 94 questions, was expanded to 195 after adjustments, generating the first version of the instrument. After the two Delphi rounds, after analysis by experts, IVC and AC1, the final version was generated with 367 questions, 27 subcategories and 9 categories. The instrument was constructed and rigorously evaluated by experts, ensuring its relevance for assessing quality, relevance of questions to subcategories, clarity and feasibility. This robust tool allows healthcare managers and professionals to assess the quality of the FC and services offered, promoting excellence in pharmaceutical care.